Efektivitas Pemberian Telur Rebus Ayam Ras Terhadap Percepatan Peyembuhan Luka Perineum - Azis, Marlina Azis; Triananinsi, Nurhidayat; Alza, Nurfaizah (JIDAN Jurnal Ilmiah Bidan, 2022)
Background : Perineal injuries are tears in the birth canal caused by the position when pressing on the mother, large baby, primigravida mother, usually caused by factors the midwife did not support properly during delivery. The healing of stitches on the perineum is influenced by perineal wound care, nutritional factors, quality of sleep and wound care and early mobilization. Objective : to find out "Effectiveness of Administering Boiled Eggs to Accelerated Perineal Wound Healing in Postpartum Mothers". Method: This type of research using the method Almost Experiment with a plan Posttest Only Control Design, The population in this study were all postpartum mothers who experienced ruptured perineal wounds and the sampling technique used was Purposive Sampling. Conducted at the Bontobangun Bulukumba Health Center in July-September 2021. Results : shows that of the 30 postpartum mothers who were sampled. Statistical test results using Test Mann-Whitney There is an effect of giving hard-boiled eggs to the accelerated healing of perineal wounds in postpartum women at the Bontobangun Bulukumba Health Center. As a recommendation to health workers to maintain and always provide information, motivation, and knowledge to postpartum mothers to consume boiled eggs of purebred chickens to accelerate the healing of perineal ruptured wounds level I-II.